1994
DOI: 10.1002/ddr.430330307
|View full text |Cite
|
Sign up to set email alerts
|

Potassium channel blockers as antiarrhythmic drugs

Abstract: Selective prolongation of cardiac repolarization i s an effective means of suppressing a variety of cardiac arrhythmias, particularly those arising from a re-entrant mechanism. Over the past several years, a variety of novel compounds have been discovered that increase cardiac action potential duration without slowing conduction. Most of these agents (e.g., dofetilide, E-4031, MK-499) act by selectively blocking the rapidly activating component of delayed rectification (IKr), although some (e.g., ibutilide, az… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 54 publications
1
35
0
Order By: Relevance
“…The same authors have shown that mutations in HERG lead to one form of hereditary LQTS. Interestingly, blockade of I kr by dofetilide, a class III antiarrhythmic agent, is thought to cause acquired LQTS [Colatsky and Argentieri, 1994]. Recently, a similar finding was obtained with sertindole, a drug exerting antipsychotic effects associated with significant increases in the corrected QT interval [van Kammen et al, 1996], which was shown to strongly inhibit HERG currents [Rampe et al, 1998].…”
Section: Long Qt Intervals and Long Qt Syndrome (Lqts)mentioning
confidence: 80%
“…The same authors have shown that mutations in HERG lead to one form of hereditary LQTS. Interestingly, blockade of I kr by dofetilide, a class III antiarrhythmic agent, is thought to cause acquired LQTS [Colatsky and Argentieri, 1994]. Recently, a similar finding was obtained with sertindole, a drug exerting antipsychotic effects associated with significant increases in the corrected QT interval [van Kammen et al, 1996], which was shown to strongly inhibit HERG currents [Rampe et al, 1998].…”
Section: Long Qt Intervals and Long Qt Syndrome (Lqts)mentioning
confidence: 80%
“…Accordingly, erg currents recorded in the prolactin-and growth hormone (GH)-secreting cell lines derived from a rat pituitary tumour (GH 3 /B 6 [9]; GH 3 [4]) or in native rat lactotroph cells [17] were described initially as inactivating, inwardly rectifying K + currents. More recently, the use of specific erg channel blockers from the class of methanesulphonanilides [15] has served to isolate these erg currents as the drug-sensitive currents [5,10,36,52] and has helped to demonstrate their physiological function. In native and clonal rat lactotroph cells, erg currents contribute to the maintenance of the resting membrane potential [7,12,52] and their inhibition by thyrotropinreleasing hormone (TRH) is thought to mediate the late phase of TRH-induced prolactin secretion (for review see [40]).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this property would also reduce the rate of spontaneous discharge in abnormal automatic tissues. However, Review K + channels in the heart: new insights & therapeutic implications even given the superficial coverage in the preceding paragraphs, it is also apparent that increasing the APD has the potential to promote EADs and trigger activity ( Figure 2) [66][67][68].…”
Section: Rationale In Antiarrhythmic Drug Developmentmentioning
confidence: 96%